The Direct Gene Injection Using of Egg Yolk Emulsion as Carrier and its Comparison with Liposomes. (Baghdad Science Journal, 2025)
The efficiency of egg yolk emulsion in coating DNA and its delivery across cellular membranes was evaluated in comparison with liposomes DOPE . The murine leukemia viral oncogene v-abl , cloned on pBR322 was used as a DNA substrate for direct injection into mice tissue . the DNA complexes were prepared by mixing the DNA with egg yolk emulsion and liposome . Each was directly injected into mice peritoneal cavity with proper control. The gene delivery was examined phenotypically by blood analysis and cytogenetic analysis . Chromosomal changes were detected in the bone marrow as from the fourth day post inoculation through the eleventh day when chromosomal ring s could be seen . this was accompanied by decrease in the WBC count , an increase in lymphoblast cells size and percentage and the discoloration of irregular RBCs . these are typical signs of acute lymphatic leukemia . Anatomical examination have indicated 25% increase in the spleen mplemented using specific primers to confirm the integration of the delivered DNA into the genomic content of the mice tissue within 48 hr post inoculation .